A Descriptive Study to Assess the Quality of Sleep among Adolescents in Selected Schools of the City in View to Prepare Information Booklet - Ajit Lokhande, Amruta; Narayan, Prabhadevi; Premanand Patole, Pratik; Ajit Lokhande, Sakshi (International Journal of Nursing Research, 2023)
Background: It is of utmost importance to understand the repercussions of unhealthy sleep pattern and the environmental factors which affect the sleep quality among adolescents so that urgent actions could be taken to mitigate the effect. A community based cross-sectional study was conducted to determine the prevalence of poor sleep quality among adolescents of an urban resettlement colony and to evaluate the association of poor sleep quality with the correlates. About 257 adolescents aged 15–18 years were involved in the study. Materials and Methods: The research design is a descriptive research design use to assess the quality of sleep among adolescents in selected schools of the city. The investigator conducted the study in selected schools of the city. The targeted population of the study will be adolescent of 10th std students. The adolescents studying at selected schools of the city. The sampling technique use in this study is non-probability purposive sampling for sample and simple random sampling technique for selecting the schools. Result: A 136 (52.91%) have moderate sleep trouble, 83 (32.29%) have light, and 38 (14.78%) have severe. There was a strong relationship between family type, number of siblings, studying in bed, school distance, and mobile phone ownership. Age, gender, religion, monthly family income, place of residence, duration of sleep time, duration of screen addiction social media, mode of travel to school, and physical difficulties were not associated with adjustment problems. Conclusion: The findings of the present study indicated that adolescent having moderate to mild level of sleep difficulty.